Analysis of Mathematical Communication Skills of High School Students on Matrix Material - Fitri Nur Ashari, Fitri Nur Ashari; Nana Karina Mayda; Desti Intan Nurhakiki; Lilis Marina Angraini (Indonesian Journal of Teaching and Learning, 2025)
This research aims to describe students’ mathematical communication skills in solving problems, especially matrix material in class XI 2 students at SMA Negeri 2 Tambang. The type of research used is a descriptive method with a qualitative approach. Data collection techniques were carried out using observation, tests, interviews and documentation methods. The test instrument used is 3 essay questions about students’ communication skills which have been validated. The subjects of this research were 28 students in class XI 2 SMA Negeri 2 Tambang. Then 4 students were selected as representatives of the research subjects based on the category of mathematical communication skills used. The results of this research show that students’ mathematical communication skills in solving questions on matrix material average 65,89 in the high category. Where there are 6 students (21,43%) in this very high category, there are 9 students (32,14%) in the high category, and there are no students in the low category.